Response and non-response to postal questionnaire follow-up in a clinical trial--a qualitative study of the patient's perspective. - Nakash, R; Hutton, J; Lamb, S; Gates, S; Fisher, J (2008)
RATIONALE, AIMS AND OBJECTIVES: Many studies have investigated response issues to postal questionnaires in educational and market research surveys. Behavioural theories have been applied to survey research to understand response decisions. Little attention has focussed specifically on response issues to postal questionnaires used to collect data in clinical trials. This qualitative study, nested within an acute injury RCT, examines factors affecting response and non-response from the clinical trial participant's perspective. METHODS: Qualitative study comprising of 22 semi-structured interviews with a purposeful sample of clinical trial participants. The sample consisted of 14 'responders' and 8 'non-responders' to postal questionnaire follow-up. Data were analysed using the Framework Method. RESULTS: Prevalent reasons for responding to the questionnaires were the perceived personal benefit, commitment to the trial and perceived obligation to respond. Altruism was also a strong motivator. There was an association between the participant's understanding of the trial and their likelihood of responding. Most non-responders were happy with the trial and gave reasons for non-response such as being 'lazy' and 'forgetful'. Participants who considered themselves to be fully recovered were less likely to respond. There also emerged a relationship between response and treatment preference. CONCLUSIONS: Saliency of the questionnaire topic is one of the most prevalent influences on response in clinical trials. This is not evident in the survey literature. Improvements in response rates may be gained by ensuring participants fully understand the trial procedures and stressing the importance of responding even if a full recovery has been made.